An Amazingly Simple, Fast and Green Synthesis Route to Polyaniline Nanofibers for Efficient Energy Storage - ur Rahman, Sami (Polymers (Basel), 2020)
The major drawbacks of the conventional methods for preparing polyaniline (PANI) are the large consumptions of toxic chemicals and long process durations. This paper presents a remarkably simple and green route for the chemical oxidative synthesis of PANI nanofibers, utilizing sodium phytate as a novel and environmentally friendly plant derived dopant. The process shows a remarkable reduction in the synthesis time and usage of toxic chemicals with good dispersibility and exceedingly high conductivity up to 10 S cm(−1) of the resulting PANI at the same time. A detailed characterization of the PANI samples has been made showing excellent relationships between their structure and properties. Particularly, the electrochemical properties of the synthesized PANI as electrode material for supercapacitors were analyzed. The PANI sample, synthesized at pre-optimized conditions, exhibited impressive supercapacitor performance having a high specific capacitance (C(sp)) (832.5 Fg(−1) and 528 Fg(−1) at 1 Ag(−1) and 40 Ag(−1), respectively) as calculated from galvanostatic charge/discharge (GCD) curves. A good rate capability with a capacitance retention of 67.6% of its initial value was observed. The quite low solution resistance (R(s)) value of 281.0 × 10(−3) Ohm and charge transfer resistance value (R(ct)) of 7.44 Ohm represents the excellence of the material. Further, a retention of 95.3% in coulombic efficiency after 1000 charge discharge cycles, without showing any significant degradation of the material, was also exhibited.